Time function DualPDA study of spray growth and droplet size-velocity profiles of chemically modified tapioca starch - Naz, M.Y. (AAGR Aerosol and Air Quality Research, 2015)
This study investigated the time based spray evolution of chemically modified tapioca starch through three full cone nozzles namely FC-2, FC-3 and FC-3.5. The objective was to study the effect of temperature, viscosity and nozzle orifice diameter on spatio-temporal droplet size-velocity profiles of the sprayed material. Owing to high viscosity, the unheated spraying medium did not exhibit any breakup over time. However, pre-spray heating of the medium at 80°C caused immediate sheet breakup near nozzle exit point at injection pressure of 5 bar. The spray growth from FC-2 was relatively faster than other tested nozzles; the unstable sheet disintegrated into fully developed spray patterns after 250 ms of the injection time. Unlike FC-2, the jet from FC-3 and FC-3.5 exhibited steady breakup at early and late injection stages, however, relatively fast breakup was seen in the middle part of the spray stream. Phase Doppler Anemometry (DualPDA) data showed a linear increase in Sauter Mean Diameter (SMD) with orifice size. At 140 mm downstream, the smallest SMD of 59 µm was obtained with FC-2 nozzle followed by FC-3 (65 µm) and FC-3.5 (83 µm). The overall SMD was decreased by 44.7 with an increase in orifice diameter from 1.19 to 1.59 mm. The droplet velocity in axial direction dropped sharply with time in the range of 100 to 300 ms, thereafter showed negligible decrease over time. Unlike this, the droplet velocity in the radial direction was dropping appreciably even after 300 ms of injection time. © Taiwan Association for Aerosol Research.